2018
DOI: 10.3390/w11010030
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Turbulence Numerical Simulation of Flow in a Stepped Dropshaft

Abstract: The dropshaft structure is usually applied in an urban drainage system to connect the shallow pipe network and the deep tunnel. By using the renormalization group (RNG) k~ε turbulence model with a volume of fluid method, the flow pattern and the maximum relative water depth over a stepped dropshaft with a different central angle of step were numerically investigated. The calculated results suggested that the flow in the stepped dropshaft was highly turbulent and characterized by deflection during the jet cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Although the k-ε turbulent models have been widely applied to flow simulations because of the fine convergence and computational efficiency [37][38][39], the RNG k-ε turbulence model proposed by Yakhot and Orzag, by providing an additional coefficient correcting the turbulent viscosity and taking into account the average rotational motion, can effectively process the strong swirling flow or curved wall jet under high Reynolds number [40]. Furthermore, regarding to previous research [2,24,41] were found that the RNG k-ε turbulence model can give the best prediction of the jet flow in such shaft spillway.…”
Section: Numerical Simulation 31 Governing Equationsmentioning
confidence: 99%
“…Although the k-ε turbulent models have been widely applied to flow simulations because of the fine convergence and computational efficiency [37][38][39], the RNG k-ε turbulence model proposed by Yakhot and Orzag, by providing an additional coefficient correcting the turbulent viscosity and taking into account the average rotational motion, can effectively process the strong swirling flow or curved wall jet under high Reynolds number [40]. Furthermore, regarding to previous research [2,24,41] were found that the RNG k-ε turbulence model can give the best prediction of the jet flow in such shaft spillway.…”
Section: Numerical Simulation 31 Governing Equationsmentioning
confidence: 99%
“…The RNG model is recommended for flows involving recirculation and interface curvature [45]- [49]. The turbulent kinetic energy and the dissipation rate Equations for this model can be written in the following way [50]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Despite some favor by engineers, few achievements about the hydraulic characteristics about the helical-step dropshaft were reported. Similar dropshafts with large-angle steps or blade-shaped steps were tested by means of experimental and numerical methods, respectively, and these case studies provided some useful information about the flow characteristics in the dropshafts (Qi et al 2018;Wu et al 2018;Sun et al 2020). Attention was also paid to the standing waves formed at the inlet of such dropshafts in the literature (Wu et al 2017).…”
Section: Introductionmentioning
confidence: 99%